Mechanisms of Anergic Inflammatory Response in Nasopharyngeal Carcinoma Cells Despite Ubiquitous Constitutive NF-κB Activation - Zhou, Xiaoying; Matskova, Liudmila; Zheng, Shixing; Wang, Xiaoxia; Wang, Yifang; Xiao, Xue; Mo, Yingxi; Wölke, Marleen; Li, Limei; Zheng, Qian; Huang, Guangwu; Zhang, Zhe; et al. (Frontiers in Cell and Developmental Biology, 2022)
Commensal microbes cross talk with their colonized mucosa. We show that microbes and their cell wall components induce an inflammatory response in cultured human mucosal cells derived from the nonmalignant nasopharyngeal epithelium (NNE) cells in vitro. NNE cells show significant induction of NF-κB with nuclear shuttling and inflammatory gene response when exposed to Gram-positive bacteria (streptococci) or peptidoglycan (PGN), a component of the Gram-positive bacterial cell wall. This response is abrogated in nasopharyngeal carcinoma (NPC)–derived cell lines. The inflammatory response induced by NF-κB signaling was blocked at two levels in the tumor-derived cells. We found that NF-κB was largely trapped in lipid droplets (LDs) in the cytoplasm of the NPC-derived cells, while the increased expression of lysine-specific histone demethylase 1 (LSD1, a repressive nuclear factor) reduces the response mediated by remaining NF-κB at the promoters responding to inflammatory stimuli. This refractory response in NPC cells might be a consequence of long-term exposure to microbes in vivo during carcinogenic progression. It may contribute to the decreased antitumor immune responses in NPC, among others despite heavy T-helper cell infiltration, and thus facilitate tumor progression.